1947
DOI: 10.1063/1.1697654
|View full text |Cite
|
Sign up to set email alerts
|

The Insulation of High Voltages in Vacuum

Abstract: Breakdown studies have been made between electrodes in high vacuum at constant voltages from 50 to 700 kv. These further demonstrate the inadequacy of the field emission theory to account generally for high voltage breakdown in vacuum. Experiments are described which investigate some of the ``total voltage'' breakdown mechanisms, including positive-ion emission by electron impact, electron emission by positive-ion impact and by photons. In the d.c. case these processes contribute to a steady interchange of cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1
3

Year Published

1954
1954
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(24 citation statements)
references
References 7 publications
1
19
1
3
Order By: Relevance
“…VAN DE GRAAFF and his collaborators as well as other authors have made many measurements to determine A and B [1], [21, [3], [4] and [5]. The results of all these measurements contradict the above theory namely AB always proved to be much smaller than 1.…”
Section: The Theory Of the Eleetron-ion Exchangecontrasting
confidence: 43%
See 1 more Smart Citation
“…VAN DE GRAAFF and his collaborators as well as other authors have made many measurements to determine A and B [1], [21, [3], [4] and [5]. The results of all these measurements contradict the above theory namely AB always proved to be much smaller than 1.…”
Section: The Theory Of the Eleetron-ion Exchangecontrasting
confidence: 43%
“…1957 produced by the strong field ocr at the cathode. Measurements have been made by VAN DE GRAArT and TRUMP concerning the breakdown occurring between a stainless steel ball anda plane electrode at voltages up to 700 kV [1]. They found that the field strength at the cathode producing a breakdown was more than 3 Mu at 0,1 mm distance of the electrodes, where as it was lower than 100 kV/cm at 70 mm distance.…”
Section: The Theory Of the Eleetron-ion Exchangementioning
confidence: 99%
“…However, the maximum of secondary electron emission coefficient of titanium, which our gun chamber is made of, is 0.9 at electron beam energy of 0.28 keV [26]. The coefficient is generally much less than the maximum for electron beam energy from 200 to 500 keV according to experimental results for other metals [27]. If one uses Y SE ¼ 0.2 instead of Y SE ¼ 50 given in the textbook [25], K ¼ 4.8 × 10 −3 is derived.…”
Section: High-voltage Insulation In Vacuum For Large Gapmentioning
confidence: 99%
“…Then, if a positive ion produces B secondary electrons and the one photon produces D secondary electrons at the cathode, a runaway phenomenon is established when AB+CD≥ 1. The authors of this hypothesis found that the secondary emission factors were too small for the development of a cumulative process [3].…”
Section: A Breakdownmentioning
confidence: 99%